VNAR single-domain antibodies specific for BAFF inhibit B cell development by molecular mimicry. (July 2016) - Häsler, Julien; Flajnik, Martin F.; Williams, Gareth; Walsh, Frank S.; Rutkowski, J.Lynn
Highlights: VNARs to BAFF with low nM potency were isolated from a semi-synthetic phage library. The CDR3 regions contain a conserved DXL motif found in all three BAFF receptors. VNARs to BAFF block B cell proliferation in response to either human or mouse BAFF. A chimeric VNAR-Fc fusion protein inhibited splenic B cell development in mice. Abstract: B cell-activating factor (BAFF) plays a dominant role in the B cell homeostasis. However, excessive BAFF promotes the development of autoreactive B-cells and several antibodies have been developed to block its activity. Bispecific antibodies with added functionality represent the next wave of biologics that may be more effective in the treatment of complex autoimmune disease. The single variable domain from the immunoglobulin new antigen receptor (VNAR) is one of the smallest antibody recognition units that could be combined with monospecific antibodies to develop bispecific agents. We isolated a panel of BAFF-binding VNARs with low nM potency from a semi-synthetic phage display library and examined their functional activity. The anti-BAFF VNARs blocked the binding of BAFF to all three of its receptors (BR3, TACI and BCMA) and the presence of the conserved DXL receptor motif found in the CDR3 regions suggests molecular mimicry as the mechanism of antagonism. One clone was formatted as an Fc fusion for functional testing and it was found to inhibit both mouse and human BAFF with equal potency ex vivo in a splenocyte proliferation assay. In mice, subchronic administration reduced the number of immature and transitional intermediates B cells and mature B cell subsets. These results indicate that VNAR single domain antibodies function as selective B-cell inhibitors and offer an alternative molecular format for targeting B-cell disorders.